2018
DOI: 10.1080/09638180.2018.1535323
|View full text |Cite
|
Sign up to set email alerts
|

Desingularization and Dequalification: A Foray Into Ranking Production and Utilization Processes

Abstract: Although some authors highlight the benefits of journal rankings, previous research is often highly critical of them, insinuating that they can lead to desingularization of academic journals (i.e., their impoverishment and standardization) and dequalification of researchers (i.e., a weakening of researchers' ability to evaluate academic research). However, as very few authors have empirically assessed these presumptions, we aim to address this gap in the literature. Based on Lucien Karpik's notions of singular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Thus, in some cases at least, journal rankings are replacing the need to think critically about the strengths and weaknesses of a particular reference source -the fact that it appears in a high-ranked journal is viewed as sufficient justification for its usage. Picard et al (2018) provides an insight into this phenomenon. They apply Karpik's analysis of the economics of singularities (2007,2010) to the case of academic articles (Karpik, 2011).…”
Section: Journal Rankings As Signals Of Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in some cases at least, journal rankings are replacing the need to think critically about the strengths and weaknesses of a particular reference source -the fact that it appears in a high-ranked journal is viewed as sufficient justification for its usage. Picard et al (2018) provides an insight into this phenomenon. They apply Karpik's analysis of the economics of singularities (2007,2010) to the case of academic articles (Karpik, 2011).…”
Section: Journal Rankings As Signals Of Qualitymentioning
confidence: 99%
“…The most notable trends in reference sources are the rise in the usage of high-ranked references sources and the journal-wide decline in references from books and monographs. Given the growing tendency for assessors and reviewers to utilise journal rankings as proxies for an article's 'quality' (Walker et al, 2018;Picard et al, 2018), it is possible that authors will seek to signal the quality of their paper to editors and reviewers by drawing heavily upon high-ranked source materials. This is a phenomenon driven by the rise of journal ranking lists, which we discussed earlier in this paper.…”
Section: Signalling In the Publication Processmentioning
confidence: 99%
“…This is, however, an open hypothesis, which seems to have been challenged by [39], who found that important papers are more and more published in non-elite journals. For a criticism of the journal impact factor, see, for example, [40]). (3) selecting documents based on principles used in so-called evidence-based research (e.g., studies based on double blind clinical trials); In evidence-based medicine (or evidence-based practice in general, EBP) the trustworthiness of claims about the effectiveness of a given treatment are classified according to the quality of the research methods employed.…”
Section: Challenges From Irmentioning
confidence: 99%
“…Finally, academics lack incentives to allocate their time and effort to engage in policy-making and produce relevant research for regulators (Singleton-Green, 2010) instead to dedicating their time to research (Fülbier et al , 2009). This impediment is especially acute for early-stage researchers, affected by the short-termism of the publication requirements to thrive in their academic careers (Picard et al , 2018). Fülbier et al (2009) suggest that producing relevant research for policy-making should also be considered when evaluating academic production; however, concerns are expressed about the possible negative consequences of adding engagement in the management of the academic performance (Bebbington et al , 2017).…”
Section: Role Of Academics In Regulationmentioning
confidence: 99%
“…We wonder whether the stupidity introduced in current research assessment exercises in which the young generation of scholars is being nurtured will create such a long-term temperament and collective dynamics required for a new epistemic community to emerge. The reign of journal rankings in Spain (as in other countries) and demands for short-term academic performance are fostering heteronomy (Picard et al , 2018), rather than the autonomy required for young scholars to develop long-term research projects, as well as a broad understanding of substantive issues, such as the role of academics and the public interest.…”
Section: Concluding Commentsmentioning
confidence: 99%